Evolution and Human Values - Wesson, Robert,; Williams, Patricia A., (Value Inquiry Book Series ;, 1995)
Initiated by Robert Wesson, Evolution and Human Values is a collection of newly written essays designed to bring interdisciplinary insight to that area of thought where human evolution intersects with human values. The disciplines brought to bear on the subject are diverse - philosophy, psychiatry, behavioral science, biology, anthropology, psychology, biochemistry, and sociology. Yet, as organized by co-editor Patricia A. Williams, the volume falls coherently into three related sections. Entitled Evolutionary Ethics, the first section brings contemporary research to an area first explored by Herbert Spencer. Evolutionary ethics looks to the theory of evolution by natural selection to find values for human living. The second section, Evolved Ethics, discusses the evolution of language and religion and their impact on moral thought and feeling. Evolved ethics was partly Charles Darwin's subject in The Descent of Man. The last section bears the title Scientific Ethics. A nascent field, scientific ethics asks about the evolution of human nature and the implications of that nature for ethical theory and social policy. Together, the essays collected here provide important contemporary insights into what it is - and what it may be - to be human.